Channel assignment strategies for multiradio wireless mesh networks issues and solutions. - Skalli, Habiba (IEEE Communications magazine)
Next-generation wireless mobile communications will be driven by converged networks that integrate disparate technologies and services. The wireless mesh network is envisaged to be one of the key components in the converged networks of the future, providing flexible high- bandwidth wireless backhaul over large geographical areas. While single radio mesh nodes operating on a single channel suffer from capacity constraints, equipping mesh routers with multiple radios using multiple nonoverlap- ping channels can significantly alleviate the capacity problem and increase the aggregate bandwidth available to the network. However, the assignment of channels to the radio interfaces poses significant challenges. The goal of channel assignment algorithms in multiradio mesh networks is to minimize interference while improving the aggregate network capacity and maintaining the connectivity of the network. In this article we examine the unique constraints of channel assignment in wireless mesh networks and identify the key factors governing assignment schemes, with particular reference to interference, traffic patterns, and multipath connectivity. After presenting a taxonomy of existing channel assignment algorithms for WMNs, we describe a new channel assignment scheme called MesTiC, which incorporates the mesh traffic pattern together with connectivity issues in order to minimize interference in multi- radio mesh networks.